(untitled) (The Research of Medical Science Review, 2024)
The aim of this study was to elucidate the role of beta-human chorionic gonadotropin in predicting pregnancy-induced hypertension, preeclampsia, and eclampsia. It was a crosssectional study over six months on 100 pregnant women between 13 and 18 weeks of gestation presenting at Abbasi Shaheed Hospital, Karachi. Serum beta-hCG levels were estimated at two time points of the second trimester to determine the relationship with hypertensive disorders. In results, it was shown that there was a close association of increased levels of β-hCG with ≥2 MoM with the progression of hypertensive complications. The values for β-hCG were remarkably greater in women who developed PIH, preeclampsia, or eclampsia. This therefore advocates the use of β-hCG as an early marker for these complications, thus improving clinical management and also reducing adverse outcomes for both the mother and the fetus